Pelatihan Manajemen Olahraga Bola Voli bagi Pelatih di Kabupaten Sleman - Sujarwo Sujarwo; Nurhadi Santoso; Abdul Mahfudin Alim (Jurnal Pengabdian Olahraga Masyarakat, 2023)
The game of volleyball is the number one sport of choice in society, therefore this sport needs to be packaged properly. The purpose of this community service is to provide education to volleyball coaches in Sleman district about volleyball sports management. Methods of community service with lectures and direct discussions. The target audience for this community service are 20 volleyball coaches. The expected knowledge from the results of this service is that activity participants have increased knowledge about volleyball sport management. Place of dedication at the "Parto" Kaliurang Sleman food stall. The instrument for exploring the trainer's knowledge uses a Google form with 10 question items. The results of the dedication show an increase in the knowledge of volleyball coaches in Sleman about volleyball sport management with an average score of: 54, increasing to a score of: 70.5. In conclusion, the trainer's knowledge of management concepts, training camp management and volleyball training management needs to be continuously improved. The outputs in this community service are Institutional Agreements (IA) and published community service journal articles. Community service needs to be carried out further to provide better education for volleyball coaches on a wider scale